KONSEP PERTANGGUNGJAWABAN MUTLAK KORPORASI SEBAB KEBAKARAN LAHAN PERKEBUNAN MENGAKIBATKAN ANCAMAN SERIUS - Rony Andre Christian Naldo; Mesdiana Purba (Jurnal Ilmiah Advokasi, 2021)
As a legal subject, in addition to rights holders, corporations are also legal obligations. In carrying out business activities estates, corporations bear a legal obligation to implement the Corporate Governance (Good Corporate Governance / GCG) and the Social Responsibility and Environment (Corporate Social Responsibility / CSR) to the realization of sustainable development. With regard to the legal obligation to implement good corporate governance and CSR activities in the plantation business, the corporation shall not open or tilling the land by burning, as fire plantation corporation can lead to a serious threat to inflict harm the environment. The fact is that on the island of Sumatera, there have been fires on plantations of various corporations resulting in a serious threat, which in Civil Law is an Act Against the Law (PMH) with the consequence of absolute liability to corporations to compensate for environmental losses. This study discusses the concept of absolute corporate accountability because plantation land fires pose a serious threat. This study is prescriptive, using normative legal methods, referring to the legal norms contained in the legislation, using secondary data. This study uses a variety of legal approaches, concepts, legal comparisons, and history. The results of the study concluded that there are 13 (thirteen) concepts related to corporate absolute responsibility because plantation land fires cause a serious threat, and there are still 4 (four) things that are weaknesses.Keywords: Accountability, Corporate, Serious Threats.